(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Over time, translation has evolved alongside technological advancements, transitioning from manual techniques to the integration of sophisticated tools and software. This exploration examines the impact, challenges, and potential of modern innovative methods and technologies in translation. By delving into machine translation, computer-assisted translation (CAT) tools, neural networks, and crowdsourcing, it elucidates how these developments are reshaping the translation landscape and fostering cross-cultural communication.